Synthesis and extended activity of triazole-containing macrocyclic protease inhibitors - Pehere, Ashok D. (2014)
Peptide-derived protease inhibitors are an important class of compounds with the potential to treat a wide range of diseases. Herein, we describe the synthesis of a series of triazole-containing macrocyclic protease inhibitors pre-organized into a β-strand conformation and an evaluation of their activity against a panel of proteases. Acyclic azido–alkyne-based aldehydes are also evaluated for comparison. The macrocyclic peptidomimetics showed considerable activity towards calpain II, cathepsin L and S, and the 20S proteasome chymotrypsin-like activity. Some of the first examples of highly potent macrocyclic inhibitors of cathepsin S were identified. These adopt a well-defined β-strand geometry as shown by NMR spectroscopy, X-ray analysis, and molecular docking studies.